Antioxidant capacity and combinatorial antimicrobial effects of Nardostachys jatamansi essential oil with conventional antibiotics against some drug resistant bacteria - Aasiya Majeed; Sanjay Guleria; Neha Sharma; Khalid Hussain Salaria; Faiqa Aiman; Bikarma Singh; Vijai Kumar Gupta (Current Research in Biotechnology, 2023)
The antibacterial and antioxidant properties of essential oils (EOs) have long been recognized. The present study was conducted to investigate the antioxidant capability of Nardostachys jatamansi essential oil and to see if it has a synergistic antimicrobial effect with antibiotics against two Gram negative (Klebsiella pneumoniae and Escherichia coli) and three Gram positive (Bacillus subtilis, Micrococcus luteus and Staphylococcus aureus) bacterial strains. Guaia-6,9-diene (11.96 %), calarene (10.44 %), jatamansone (8.11 %), α-gurjunene (7.42 %), valencene (6.46 %), α-maaliene (5.24 %), sprojatamol (5.06 %), and caratol (5.06 %) were found to be the primary components of N. jatamansi EO. According to antioxidant studies, N. jatamansi EO has moderate DPPH radical scavenging activity, reducing power, and ferric reducing antioxidant power. Similarly, N. jatamansi EO also showed significant antibacterial activity, with inhibition zones, MIC, and MBC values ranging from 10.5 ± 0.5 to 14.0 ± 0.4 mm, 1.5 to 3.1 mg/mL, and 1.8 to 3.5 mg/mL respectively. The results of N. jatamansi EO interactions with conventional antibiotics revealed that amoxicillin, erythromycin, chloramphenicol, and ampicillin MICs were reduced by 5 to 10 fold, 4 to 9.09 fold, 4 to 10.5 fold, and 4 to 8.0 fold, respectively. The findings of this study are noteworthy because no previous reports of N. jatamansi EO's synergistic interaction with conventional antibiotics have been published, and therefore may constitute an important strategy for addressing problem of drug resistant bacteria.